Unlocking the potential of antisolvent-free perovskite solar cells: modulating crystallization and intermediates through a binary volatile additive strategy - Zhou, B; Zhao, P; Guo, J; Qiao, Y; Hu, S; Guo, X; Liu, J; Li, C (Elsevier, 2024)
High-quality perovskite polycrystalline thin films are generally achieved through antisolvent-assisted crystallization, a crucial process that facilitates desolvation. However, antisolvent method is limited by issues of toxicity and fabrication complexity. Here, we introduce a “binary volatile additive” strategy using methylammonium chloride (MACl) and trifluoroacetamide (TFAA) in dimethylformamide/N-methyl-2-pyrrolidone co-solvent system, enabling end-to-end management of antisolvent-free crystallization process. Combining in-situ characterizations and DFT calculations, we prove that TFAA adjusts coordination with perovskite intermediates, facilitating solvent removal and promoting the formation of nuclei, while MACl reduces the formation energy of α-phase formamidinium-based perovskite. Moreover, TFAA not only releases the residual strain caused by MACl, but also in combination with MACl, synergistically widens crystallization window and regulates ripening process, allowing for precise fabrication of homogeneous perovskite films with suppressed defects. By employing the “binary volatile additive” approach, we achieve perovskite solar cells with a power conversion efficiency up to 22.4% and elongated storage life (93% PCE retention over 1000 hours). Our study offers a simple and sustainable approach to produce high-quality perovskite films without the acquisition of antisolvent, streamlining the fabrication process.